Distinct positions underpin ecosystem services for poverty alleviation. Issue 3 (30th May 2020) - Howe, Caroline; Corbera, Esteve; Vira, Bhaskar; Brockington, Daniel; Adams, William M.
Abstract: As the concept of ecosystem services is applied more widely in conservation, its users will encounter the issue of poverty alleviation. Policy initiatives involving ecosystem services are often marked by their use of win-win narratives that conceal the trade-offs they must entail. Modelling this paper on an earlier essay about conservation and poverty, we explore the different views that underlie apparent agreement. We identify five positions that reflect different mixes of concern for ecosystem condition, poverty and economic growth, and we suggest that acknowledging these helps to uncover the subjacent goals of policy interventions and the trade-offs they involve in practice. Recognizing their existence and foundations can ultimately support the emergence of more legitimate and robust policies.